An Iterative Image Reconstruction for Differential X-ray Phase-contrast Computed Tomography (Journal of Fiber Bioengineering and Informatics, 2015)
The last decade saw the growth of the use of X-ray Phase-contrast Computed Tomography (PCT)imaging. Differential X-ray Phase-contrast CT (DPCT) has shown bright prospect for clinical use inrecent years, but how to best reconstruct the phase-contrast tomographic image from incomplete orinconsistent projections remains challenging. We designed an iterative image reconstruction method forDPCT utilizing compressed sensing. This proposed method reconstructs the phase-contrast tomographicimage of the refractive index decrement gradient with acceptable accuracy and image quality even whenthe projection data is undersampled or noisy. Real data experiments indicate this proposed methodis accurate and practical and outperforms the analytic filtered back-projection reconstruction. Thismethod shows potential for X-ray DPCT facilities in low dose tomography and fast acquisition imaging.
Keywords: X-ray Phase-contrast Imaging; Computed Tomography (CT); Compressed Sensing; Low Dose Tomography; Fast Acquisition Imaging